English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

it says find k

x^2 + kx - 39 = 0: r1=3


*r1, the 1 is small and is under the r to the bottom right

2006-12-03 14:37:25 · 3 answers · asked by garnett12341234 1 in Science & Mathematics Mathematics

3 answers

(x - 3)(x + 13)
x^2 + 13x - 3x - 39
x^2 + 10x - 39

k = 10

2006-12-03 15:03:40 · answer #1 · answered by Sherman81 6 · 0 0

Solution:

Since r1 = 3, it follows that one of the factors is (x - 3)

So the factors will look like:

(x - 3) (x + 13) = 0

Expanding this equation, we get:

(x - 3)*x + (x-3)*13 = 0
x^2 -3x + 13x - 39 = 0
x^2 + 10x - 39 = 0

So k = 10

2006-12-03 22:49:05 · answer #2 · answered by euclidjr 2 · 0 0

r_1 is one of the roots.

the sum of the roots is the coefficient of the second largest power in the variable over the leading coefficient:

k/1 = k -> doesnt help us a lot

the product of the roots for an even degree is the constant over the leading coefficient:

-39/1 ->-39

to find the sum simply divide the factor (x-3) into your quadratic, then add the root you get to 3.

2006-12-03 22:50:15 · answer #3 · answered by AibohphobiA 4 · 0 0

fedest.com, questions and answers